PERAN KEPALA DAERAH DALAM MEMBANGUN DAERAH - Permata Hartanto, Rima Vien (PKn Progresif, 2015)
Throughout the history, the office and presence of regional leader are very strategic. The authority of regional leader always represents two functions, as the instrument of central government and local government. Regional leader is a significant component for the success of national development program and is a managerial figure who determines the effectivenessof local government?s goal achievement. Therefore, local governance process is synergistically determined by the role of regional leader; so that the leadership of regional leader within the bureaucracy plays an important role in building strong governance. Surakarta under the leadership of JokoWidodo as the Mayor and FX.Hadi Rudyatmo as the Deputy Mayor is a good model of regional leaderthat succeed in managing the district of Surakarta. The success is marked by so many achievements and awards received by the district of Surakarta. It means there is something special in the process of governance in Surakarta  so that this best practice of successful public policy by The Mayor and Deputy Mayor of Surakarta can be a replicated by other cities.